PERBEDAAN HASIL BELAJAR SISWA YANG DITERIMA MELALUI PILIHAN MINAT PADA JURUSAN TEKNIK BANGUNAN TAHUN AJARAN 2014/2015 SMK NEGERI 5 PADANG - 617-623 , Meri Hasibuan (Universitas Negeri Padang, 2015)
ABSTRACT Acceptance of new students was held on every year in SMK 5 Padang. Through a choice selection of interest, this school only selecting new students based on the value of Final Exam. However, there are still many students graduate from this screening method that has the problem on learning results. In addition, students' motivation in learning is still low. This study aims to look at the differences in the results of class X student Building Engineering of the academic year 2014/2015 SMK 5 Padang by passing the PSB option interest. This type of research is comparative. The hypothesis of this study that there are differences in learning results in class X Building Engineering Department of the academic year 2014/2015 SMK 5 Padang by passing through a choice of interest. The population in this study were all students of class X Building Engineering Department of the academic year 2014/2015 SMK 5 Padang that pass through the selection of 90 people. A sampling technique that total sampling with a sample of 90 people. The type of data in this research is secondary data, the results of class X student of SMK Negeri 5 Padang academic year 2014/2015. Test data analysis performed by Mann Whitney U test, to test the independence of two samples on an ordinal scale. Results of research by Mann Whitney U showed that there was no difference in learning outcomes of students who graduated either in option 1 and 2, 1 and 3, and 2 and 3 on the selection choice of interest. Keywords: Options interests, learning results